MPPT PV Modeling with ANN Using Matlab Simulink - Bambang Dwinanto (Eduvest - Journal of Universal Studies, 2022)
Paper this presents the Matlab /Simulink model of PV module and maximum system tracking point power (MPPT). Maximum Power Point Tracking (MPPT) is something method for track (track) the point power a source energy to produce power maximum . one _ MPPT method that can applied to a photovoltaic system is fractional open voltage method . Common problems _ happen to the system source voltage using photovoltaic is not suit Among load and power generated . _ This thing occur due to source sourced voltage _ of photovoltaic is strongly influenced by the conditions radiation and temperature around . For resolve Thing this so required something battery for keep the power that will used as source voltage . There are various methods and ways for realize MPPT control , including perturb and observe, incremental conductance, constant voltage, and parasitic capacitance . Method the have many disadvantages , among others , quite expensive and difficult implemented . There are various method for realize MPPT controller , one of them is with use network nerves imitation (ANN). MPPT ANN technique effective increase speed tracking and upgrading power output per day from one PV modules from 3.37 kW h to 3.75 kW h, i.e. percentage 11.28%. Enhancement power output from PV prove tested advantages _ with techniques that can reduce sufficient cost _ big of the generated kWh